2018
DOI: 10.15288/jsad.2018.79.725
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Adolescent Alcohol Involvement: Evidence for a Gene–Environment Interaction

Abstract: Adolescence is an optimal developmental stage for examining the interplay of environmental factors and the genetic risk for alcohol involvement. The current study aimed to examine how socioeconomic status might interact with genetic risk for alcohol involvement among adolescents. Method: A total of 839 same-sex adolescent twin pairs (509 monozygotic and 330 dizygotic) from the 1962 National Merit Tw in Study completed a questionnaire containing items assessing alcohol involvement. Tw ins were approximately 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…First, in a national sample of individuals affected with AUD and DUD, we found, consistent with prior studies of the phenotype of educational attainment (Davis & Slutske, 2018; Hamdi et al, 2015), that high GAEA attenuated the impact of genetic liability on the risk of both AUD and DUD. This effect was clearly seen in the slope of the FGRS curves depicted in Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, in a national sample of individuals affected with AUD and DUD, we found, consistent with prior studies of the phenotype of educational attainment (Davis & Slutske, 2018; Hamdi et al, 2015), that high GAEA attenuated the impact of genetic liability on the risk of both AUD and DUD. This effect was clearly seen in the slope of the FGRS curves depicted in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…High educational attainment, socio-economic status (SES), and intelligence are consistently associated with lower levels of alcohol consumption and/or problematic drinking in Sweden (Sjölund, Hemmingsson, & Allebeck, 2015a; Sjölund, Hemmingsson, Gustafsson, & Allebeck, 2015b; Wennberg, Andersson, & Bohman, 2002; Zettergren & Bergman, 2014), and similar trends are typically seen elsewhere (Barr, Silberg, Dick, & Maes, 2018; Müller et al, 2013; Rogne, Pedersen, & Von Soest, 2021). In two twin studies, the heritability of alcohol consumption was moderated by SES such that heritability was lower in subjects with higher SES (Davis & Slutske, 2018; Hamdi, Krueger, & South, 2015).…”
mentioning
confidence: 99%
“…For example, the impact of genes is enhanced in countries with low taxes on alcohol sales and in relationships with heavy drinking partners, and decreased in more restrictive contexts such as social groups with a high proportion of drinking abstention and among youth whose access to alcohol is controlled (Dick and Kendler, 2012, Savage et al, 2018b). These moderation effects also appear to differ across the specific dimensions of AM, with, for example, stronger genetic influences on alcohol consumption but weaker genetic influences on AUDs under conditions of high socioeconomic status (SES) (Davis and Slutske, 2018, Barr et al, 2018, Pasman et al, 2020). Strong links between trauma exposure and alcohol in the twin literature (Magnusson et al, 2012) prompted early molecular G×E research which showed that trauma moderates the effects of candidate genes involved in stress response (Baranger et al, 2016, Lieberman et al, 2016) and alcohol metabolism (Sartor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the impact of genes is enhanced in countries with low taxes on alcohol sales and in relationships with heavy drinking partners, and decreased in more restrictive contexts such as social groups with a high proportion of drinking abstention and among youth whose access to alcohol is controlled Kendler, 2012, Savage et al, 2018b). These moderation effects also appear to differ across the specific dimensions of AM, with, for example, stronger genetic influences on alcohol consumption but weaker genetic influences on AUDs under conditions of high socioeconomic status (SES) (Davis and Slutske, 2018, Barr et al, 2018, Pasman et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that environmental influences are time-specific and variable whilst genetic influences remain relatively stable across time and largely contribute to the stability of alcohol use, however, still rather represent a predisposition than an inescapable fate (Hines, Morley, Mackie, & Lynskey, 2015;Zheng, Brendgen, Dionne, Boivin, & Vitaro, 2019). The interplay between genes and environment is nicely illustrated in a study by Davis and Slutske (2018), in which the genetic influence was reduced from about 50% of explained variance to about 2% of explained variance depending on low or high family income respectively.…”
Section: Introductionmentioning
confidence: 99%